Self-assembled helical superstructures of polystyrene-b-poly(2-vinyl pyridine) with inversed helicity from induced chirality. (August 2021) - Yang, Che-Chia; Puneet, Puhup; Lin, I-Ming; Chiang, Yeo-Wang; Ho, Rong-Ming
Abstract: This work aimed to examine the self-assembling behaviors of polystyrene-b-poly(2-vinyl pyridine) (PS-P2VP) complexed with chiral dopants, R-/S-mandelic acid (R-/S-MA). Induced vibrational circular dichroism (VCD) due to intra-chain chiral interaction suggests the formation of helical P2VP with preferred handedness by complexation with R-/S-MA, demonstrating the induced circular dichroism (ICD) behaviors for the C-C single bond without high-degree tacticity. Owing to the microphase separation, helical superstructures with controlled helicity could be formed from the self-assembly of PS-P2VP with ICD. Most interestingly, the self-assembled helical ribbon exhibits reversed helical sense to the helical P2VP, as evidenced by induced VCD through inter-chain chiral interaction and rationalized using cholesteric hard-core model due to a large value of P/d ratio. Graphical abstracts: Image, graphical abstract